Tinjauan Undang-Undang Nomor 1 Tahun 1974 dan KHI Terhadap Praktik Peminangan Adat Minangkabau - Dwi Aryani, Puput; Rahmat, Sulthon (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2023)
This paper aims to find out how Law No. 1 of 1974 and KHI view the Minangkabau Traditional Engagement Practice. This is based on the behavior and opinions of some people who are pro and contra to this engagement practice. The author finds that these two attitudes seem to contradict each other and are sometimes in line with the applicable law. Where the pro opinion tends to the order of community life based on applicable customary law, while the contra opinion tends to the UUP and KHI whose regulations are sometimes not in line with Minangkabau customary rules. This research is expected to provide an understanding of the legal dualism of Minangkabau customary engagement practices. This research uses a literature study with the object of research is the application of Minangkabau customary marriage practices. From this research it can be concluded that, the Minangkabau customary engagement practice uses a matrilineal system whose customary rules are not in line with KHI. However, this does not cause a decline in its existence, there are still many young people who still uphold their original culture and are not eroded by the times.